Sharia Cooperative Promotion Strategies and their Role in Increasing Membership Growth - Nugroho, Anton Priyo; Wahdi, Nirsetyo; Sudewa, Jaka; Ratnawati; Sattar (Journal La Sociale, 2026)
Sharia cooperatives play a strategic role in promoting inclusive economic development by providing financial services aligned with Islamic principles. In recent years, increasing competition among financial institutions has compelled Sharia cooperatives to adopt more adaptive and persuasive promotional strategies to attract new members. This study aims to qualitatively explore the promotional dynamics of Sharia cooperatives and examine how various promotional instruments contribute to membership growth. Unlike conventional studies that rely primarily on qualitative surveys, this research employs an qualitative analytical approach to capture complex patterns, interactions, and non-linear relationships among promotional variables based on empirical field data. The study focuses on key promotional, including social media promotion, community-based marketing, trust-building communication, and perceived Sharia compliance. Data were collected through in-depth interviews, focus group discussions, and institutional documentation from selected Sharia cooperatives. The findings are expected to provide contextual insights into the integration of Islamic values with data-driven promotional strategies. This research contributes to the development of innovative promotion models for Sharia cooperatives by highlighting the potential of artificial intelligence in strengthening strategic decision-making. Practically, the results are anticipated to offer policy-relevant insights for cooperative managers and regulators seeking to enhance the sustainability and competitiveness of Sharia-based financial institutions.